2018
DOI: 10.3390/jcm7100327
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intensity of Sleep Bruxism in Arterial Hypertension

Abstract: Sleep bruxism (SB) is a masticatory muscle activity during sleep that is characterized as rhythmic (phasic) or non-rhythmic (tonic). The recent hypothesis on the etiology of SB supports the role of the central and autonomic nervous systems. Therefore, in this study, we aimed to assess the intensity of SB in patients with arterial hypertension. A total of 70 adults participated in this study: 35 patients with hypertension (study group) and 35 normotensive subjects (control group). Data were recorded using home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 47 publications
3
43
0
Order By: Relevance
“…The third group or external factors are constituted by caffeine consumption, smoking, alcohol intake, and drug use. 12 Furthermore, the multifactorial origin of bruxism involves medical conditions and disorders such as obstructive sleep apnea (OSA), 13,14 diabetes, 14 increased body mass index (BMI), hypertension, 15,16 thyroid diseases, sleepiness, and snoring. 17 The contraction of cardiovascular diseases (CVDs) increases with age among patients with an established CVD and those at an increased risk of developing a CVD.…”
Section: Introductionmentioning
confidence: 99%
“…The third group or external factors are constituted by caffeine consumption, smoking, alcohol intake, and drug use. 12 Furthermore, the multifactorial origin of bruxism involves medical conditions and disorders such as obstructive sleep apnea (OSA), 13,14 diabetes, 14 increased body mass index (BMI), hypertension, 15,16 thyroid diseases, sleepiness, and snoring. 17 The contraction of cardiovascular diseases (CVDs) increases with age among patients with an established CVD and those at an increased risk of developing a CVD.…”
Section: Introductionmentioning
confidence: 99%
“…However, even with the research results positioning portable EMG devices among the most reliable and easy to use methods for diagnosing bruxism, the complexity, sensitivity, and irreplaceable value of audio-video recordings in PSG still places it as the most detailed and valid diagnostic method for sleep bruxism. Furthermore, there have been developments in the form of portable sleep monitoring devices, e.g., the Nox-T3 Portable Sleep Monitor (Nox Medical, Reykjavik, Iceland), which seem to answer the need for simplified, yet detailed, diagnostic equipment in terms of sleep bruxism and sleep medicine in general [6,70].…”
Section: Discussionmentioning
confidence: 99%
“…An estimated prevalence of bruxism ranges from 8% to 31% in the adult population [1], and some research states that bruxism affects women more commonly than men, due to women being more sensitive to stress and reporting it more often [2,3,4]. In accordance with the American Academy of Sleep Medicine (AASM), bruxism is defined as a “repetitive jaw-muscle activity characterized by clenching or grinding of the teeth and/or by bracing or thrusting of the mandible” [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of risk factors have been identified for SB, which include caffeine, smoking, stress, alcohol, anxiety, age, drugs [6,7], and obstructive sleep apnea [8]. Recently, our research group found that diabetes [8], body mass index (BMI), and hypertension [9] act as independent risk factors for SB [9]. In a study by Nashed, SB was shown to be associated with an increase in blood pressure during the rhythmic activity of the masticatory muscles [10].…”
Section: Introductionmentioning
confidence: 99%